MIDWIVES' COMPLIANCE TO THE STANDARD OPERATING PROCEDURE ON THE EARLY IDENTIFICATION OF PREECLAMPSIA - Dian Islami (Universitas Airlangga, 2019)
Background: The main cause of maternal mortality in East Java was pregnancy hypertension (Preeclampsia/eclampsia). The percentages of pregnant women treated with early identification of preeclampsia care according to Standard Operating Procedure (SOP) in primary healthcare centers of Surabaya was still low (26%). Aim: This study aimed to analyze the factors that influence midwives' compliance towards the SOP implementation of early identification of preeclampsia in primary healthcare centers of Surabaya. Methods: The study was an observational analytic research with cross sectional. The samples chose midwives at 20 primary healthcare centers as the informants. The independent variables are individual factors, organizational factors, and psychological factors of the midwives. The dependent variable was midwives' compliance towards the implementation of SOP for early identification of preeclampsia. Results: The results of this study show 35% of primary healthcare centers have not implemented the SOP of early identification of Preeclampsia in pregnant women. The results also showed that the majority of primary healthcare centers in Surabaya had midwives aged 31 to 40 years (50%), graduated from a Diploma 3 education (95%), contracted status (85%) and still worked less than six years (60%). Conclusion: This research highlighted the midwives' compliance which was determined not only by individual internal factors, but also organizational behavior. Preparing early identification of preeclampsia mechanisms, facility, and equipment proposal is important to do with the implementation of supportive system, quality control team, reward as well as punishment system.   Keywords: Compliance, Early identification, Midwives, Preeclampsia, SOP.